EKSTRAK BATANG “AKAR KAIK-KAIK” ( Uncaria Cordata Lour. ) Merr SEBAGAI ANTIDIABETES PADA MENCIT YANG DI INDUKSI ALOKSAN - Kirent Arikhsa Putri; Nurhamidah; Agus Sundaryono (University of Bengkulu, 2025)
[EXTRACT OF “KAIK-KAIK ROOT” STEM (Uncaria Cordata Lour.) Merr AS AN ANTIDIABETES IN ALLOXAN-INDUCED MICE] This research aims to determine the effect of giving kaik-kaik root stem extract (Uncaria cordata Lour. Merr) on the blood sugar levels of mice (Mus musculus) induced by alloxan. This reseacrh began with a phytochemical test conducted to determine the secondary metabolite compounds contained in the root stem of kaik-kaik (Uncaria cordata Lour. Merr). Extraction is done by maceration method. Antidiabetic activity test was carried out on male mice induced by alloxan. The results of the phytochemical test showed that the stem extract of Uncaria cordata contained alkaloids, flavonoids, tannins, saponins and terpenoids. The results of the antidiabetic activity test showed that the Uncaria cordata stem extract was able to reduce blood glucose levels in alloxan-induced mice with the optimal dose of Uncaria cordata stem extract at a dose of 0.043 g/kgBB. Based on the results of this study, it can be concluded that the stem of Uncaria cordata has antidiabetic activity. Keywords: Antidiabetic, Kaik-Kaik Root Stem, Uncaria cordata Lour. Merr, Alloxan